Governança corporativa e disclosure socio-ambiental nas companhias listadas na BM&BOVESPA. - Rêgo, Breno Penha (2017)
With the evolution of corporate governance in Brazil, the organizations' concern with their stakeholders has grown, especially about the dissemination of socio-environmental information. The agency theory and the legitimacy theory try to explain this phenomenon, either by the approach of the agency conflict reduction and informational asymmetry, or by the approach of the organizational seek for legitimacy before society. Therefore, this study has the objective of analyzing the influence of the corporate governance structure on the socio-environmental disclosure of Brazilian listed companies. Hence, it is considered that corporate governance influences the disclosure of Brazilian listed companies (research’s general hypothesis). It is a descriptive research, predominantly quantitative, using the documentary procedure, in which descriptive and inferential statistics were applied. The sample embraces 111 companies, included in 99 sustainability reports, released in 2015, with information for the year 2014. The major data sources were sustainability reports and annual reports, reference forms and financial statements for the exercise ended in 2014, in addition to the theoretical portfolio of the Corporate Sustainability Index (ISE). The research variables included the corporate governance structure, with the board size, independent directors on the board, presence of audit committee, presence of sustainability committee and external audit firm, as well as some institutional characteristics, such as presence in the ISE index and companies’ size, age and sector. The results indicate that the presentation of the socio-environmental information, whether through a specific sustainability report or the annual reports, does not differ in terms of the quality of the information disclosed. It can be concluded that, in general, the corporate governance structure was not able to influence the level of socio-environmental disclosure of the Brazilian listed companies surveyed. However, it should be noted that only the independent directors on the board and the presence in ISE index presented statistically significant results regarding the influence on the level of social and environmental disclosure of the sample. So, these results confirm some national studies, indicating that the relationship between corporate governance and socio-environmental disclosure seems to be more evident in international terms than in the Brazilian governance environment.